A sociological exploration of the parents’ educational constructions for children afflicted with hearing loss - Achmad Hidir; T. Romi Marnelly; Rahman Malik (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Inclusive education is essential, but many people still discriminate against children with special needs, including deaf children. At first glance, deaf children are no different from other children. Therefore, their parents also want their children to grow and develop like others. This study aims to explore this issue using qualitative methods to understand parents' social constructions regarding their children's education. The research was carried out at SLB Sri Mujinab Pekanbaru, one of the oldest special schools in Pekanbaru. Participants were selected purposively, employing interaction analysis techniques. This study found that deaf children also achieve various milestones and are not intellectually inferior. Their parents hope that their children grow and develop like typical children. The widespread use of social media and services for children with special needs has compelled parents to learn extensively to support their children's growth and development so that they can become independent.